EFEKTIVITAS TERAPI APPLIED BEHAVIOR ANALYSIS (ABA) DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK AUTISME DI SKH 2 KOTA SERANG - Astria Nova Khoirini; Yahdinil Firda Nadirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition that affects communication, social interaction, and information processing. Applied Behavior Analysis (ABA) is recognized as the gold standard for autism intervention with the strongest empirical evidence base. This study aims to evaluate the effectiveness of ABA therapy in improving the cognitive abilities of children with autism at SKH 2 Kota Serang. The study used a qualitative approach with a descriptive method. The research subjects consisted of two children with autism and one accompanying teacher, selected through purposive sampling. Data were collected through non-participatory observation and in-depth interviews, then analyzed using Miles and Huberman's interactive analysis model. After undergoing ABA therapy for 6 months with an intensity of 3-4 sessions, there was a significant increase in the children's cognitive abilities. The success of the therapy was supported by the use of prompting, fading, reinforcement, and task analysis techniques. Key success factors included adequate therapist qualifications, an ideal therapist-child ratio (1:1 or 1:2), active parental involvement, and consistent application of behavioral strategies in various settings.